Władze i dziennikarze. Stowarzyszenie Dziennikarzy Polskich w 1956 roku - Przeperski, Michał (Pamięć i Sprawiedliwość, 2014)
The Polish Journalists’ Association was one of many industrial vocational organizations set up in Poland at the beginning of the 1950s. Based on the Soviet model, Polish authorities created a network of creative organizations which were something between a trade union and a social club where every member would monitor another. What is so special about the Polish Journalists’ Association? First of all, the fact that its members were the propagandists most active in the building of foundations of the totalitarian communist system. Their situation was quite particular in the break-through year of 1956. The year 1956 and the deep political and economic changes it brought along were both an opportunity and a threat to them. It was an opportunity because they could flourish and write without a gag in the mouth. It was a threat because the careers of the most committed stalinism champions would break one after another. The article analyzes the changeable political commitment of PJA in 1956. An important role is played by considerations on differences between journalists from the peripheral regions and those active in the centre of Polish reality, presented against a broader backdrop of the political situation in the People’s Republic of Poland. Finally, the text answers this question: what was the actual role of PJA in 1956? It also outlines the problems the Association had to face over the following years.